Households experiencing catastrophic costs due to tuberculosis in Uganda: magnitude and cost drivers - Winters Muttamba; Racheal Tumwebaze; Levicatus Mugenyi; Charles Batte; Rogers Sekibira; Abel Nkolo; Achilles Katamba; Simon Kasasa; Robert Kaos Majwala; Stavia Turyahabwe; Frank Mugabe; Kaggwa Mugagga; et al. (BMC, 2020)
Abstract Background Tuberculosis (TB) patients in Uganda incur large costs related to the illness, and while seeking and receiving health care. Such costs create access and adherence barriers which affect health outcomes and increase transmission of disease. The study ascertained the proportion of Ugandan TB affected households incurring catastrophic costs and the main cost drivers. Methods A cross-sectional survey with retrospective data collection and projections was conducted in 2017. A total of 1178 drug resistant (DR) TB (44) and drug sensitive (DS) TB patients (1134), 2 weeks into intensive or continuation phase of treatment were consecutively enrolled across 67 randomly selected TB treatment facilities. Results Of the 1178 respondents, 62.7% were male, 44.7% were aged 15-34 years and 55.5% were HIV positive. For each TB episode, patients on average incurred costs of USD 396 for a DS-TB episode and USD 3722 for a Multi drug resistant tuberculosis (MDR TB) episode. Up to 48.5% of households borrowed, used savings or sold assets to defray these costs. More than half (53.1%) of TB affected households experienced TB-related costs above 20% of their annual household expenditure, with the main cost drivers being non-medical expenditure such as travel, nutritional supplements and food. Conclusion Despite free health care in public health facilities, over half of Ugandan TB affected households experience catastrophic costs. Roll out of social protection interventions like TB assistance programs, insurance schemes, and enforcement of legislation related to social protection through multi-sectoral action plans with central NTP involvement would palliate these costs.